The effect of video clips and role play on students’ listening and speaking skills - Diana Rizky Amalia; Ririn Ambarini; Sri Wahyuni (English Learning Innovation, 2026)
Developing listening and speaking skills is essential in English as a Foreign Language (EFL) education. However, a significant gap persists between formal classroom instruction and real-life oral interaction due to limited exposure to authentic language environments. This study examined the empirical effectiveness of integrating authentic video clips into structured role-play activities to enhance students’ speaking and listening skills concurrently. Using a quasi-experimental non-equivalent control group design, the investigation involved two intact eighth-grade classes at SMPN 8 Semarang. The experimental group received integrated video modeling and role-play simulations, while the control group followed traditional, teacher-centred instruction. Data from standardised pre-tests and post-tests were analyzed using Multivariate Analysis of Covariance (MANCOVA). The multivariate omnibus analysis revealed a statistically significant simultaneous effect of the dual-strategy intervention on the dependent variables (p=.007). Follow-up univariate analyses indicated that the treatment had a highly significant independent effect on students’ speaking achievements (p=.002) with a substantial effect size. Conversely, performance gains in listening did not differ significantly from the control condition (p=.472). These findings imply that while integrated multimedia and interactive simulations are highly effective for accelerating active oral production, developing receptive auditory decoding faculties requires more prolonged instructional exposure.